Interdependencies of quarter report announcement in stock price volatility: comparative analysis of construction industries/ Mohamed Farhan Mohamed Firdaus - Mohamed Firdaus, Mohamed Farhan (2017)
This paper is study of the effect of quarter announcement result to the stock price of 10 listed companies in construction sector in Bursa Malaysia beginning period of 2010 until 2016. Past study have shown some of the quarter announcement does have its significant effects towards the stock price and some of the study found there is no correlation between quarter result and stock price. Most of the researches focus on determining the movement of the stock price by examining pre and post of quarter report. This study has come out with different ways of study. This study focus on the financial elements contains in the quarter announcement result. The elements such revenue, net profits, earning per share, net tangible asset and return on equity are selected in order to pursue two research objectives which is to identify whether the elements selected do have relationship with the stock price and which of the element affect most to the stock price. Investors may rely on several ways in making their investment decision such technical analysis, fundamental analysis, news and quarter report which contains all updated information about the company.